2016
DOI: 10.1038/srep29073
|View full text |Cite|
|
Sign up to set email alerts
|

Beyond the brain-Peripheral kisspeptin signaling is essential for promoting endometrial gland development and function

Abstract: Uterine growth and endometrial gland formation (adenogenesis) and function, are essential for fertility and are controlled by estrogens and other regulators, whose nature and physiological relevance are yet to be elucidated. Kisspeptin, which signals via Kiss1r, is essential for fertility, primarily through its central control of the hypothalamic-pituitary-ovarian axis, but also likely through peripheral actions. Using genetically modified mice, we addressed the contributions of central and peripheral kisspept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…To determine whether gland development and function were impaired in the KO uterus, the expression of FOXA2 was assessed by immunohistochemistry (IHC) in the d 4pregnant CTRL and KO uteri. FOXA2 is strongly expressed on the glandular epithelium and is a critical regulator of endometrial gland development and function (15,27,28). Results indicate that FOXA2 expression was similar between the CTRL and KO uteri ( Fig.…”
Section: Embryos Do Not Implant In the Uteri Of Gnaq Pgr-cre -Ko Femalesmentioning
confidence: 85%
See 4 more Smart Citations
“…To determine whether gland development and function were impaired in the KO uterus, the expression of FOXA2 was assessed by immunohistochemistry (IHC) in the d 4pregnant CTRL and KO uteri. FOXA2 is strongly expressed on the glandular epithelium and is a critical regulator of endometrial gland development and function (15,27,28). Results indicate that FOXA2 expression was similar between the CTRL and KO uteri ( Fig.…”
Section: Embryos Do Not Implant In the Uteri Of Gnaq Pgr-cre -Ko Femalesmentioning
confidence: 85%
“…Perhaps the first evidence was from the study by Warsop et al (38), which reported that during early pregnancy in the guinea pig, Ga q/11 uterine membrane content dropped in early pregnancy relative to the nonpregnant uteri but rose significantly as pregnancy progressed. Later studies from genetically modified mice lacking Ga q/11 -coupled LPAR3 and KISS1R further suggested possible roles in regulating the final acquisition of uterine receptivity and embryo implantation (12,13,15). However, because LPAR3 also couples to Ga i/0 , it could not be ruled out that it was a disruption of the LPAR3/ Ga i/0 signaling pathway in the LPAR3 KO that prevented the full acquisition of uterine receptivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations